2016
DOI: 10.1002/ehf2.12091
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width and mortality in acute heart failure patients with preserved and reduced ejection fraction

Abstract: BackgroundElevated red blood cell distribution width (RDW) is a valid predictor of outcome in acute heart failure (AHF). It is unknown whether elevated RDW remains predictive in AHF patients with either preserved left ventricular ejection fraction (LVEF) ≥50% or reduced LVEF (<50%).Methods and resultsProspective local registry including 402 consecutive hospitalized AHF patients without acute coronary syndrome or need of intensive care. The primary outcome was all‐cause mortality (ACM) at 1 year after admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 28 publications
2
57
0
1
Order By: Relevance
“…CRAS in patients at discharge was an independent predictor of re-admission for HF and mortality. 19 Literature review shows that in the European Society of Cardiology-Heart Failure (ESC-HF) pilot registry, 26% (1300/5000) of AHF patients had CKD. 17 Left ventricular dysfunction and renal dysfunction are independent predictors of poor prognosis and higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…CRAS in patients at discharge was an independent predictor of re-admission for HF and mortality. 19 Literature review shows that in the European Society of Cardiology-Heart Failure (ESC-HF) pilot registry, 26% (1300/5000) of AHF patients had CKD. 17 Left ventricular dysfunction and renal dysfunction are independent predictors of poor prognosis and higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sotiropoulos et al reported that high RDW is associated with long-term mortality in patients with preserved, but not reduced ejection fraction. [19]. The results of prospective studies with long-term follow-up (Tromsø and National Health and Nutrition Examination Survey) demonstrate that high RDW values are associated with increased risk of myocardial infarction (MI) and mortality due to CAD in the general population [15,16], and in elderly patients without age-associated diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline RDW is reported to independently predict the prognosis of patients with acutely decompensated HFpEF, and the same is true in patients hospitalized for the treatment of HF with highly reduced (≤35%) EF . However, in the comparison of HFrEF with HFpEF, all‐cause mortality increased with elevating RDW in patients with HFpEF, but not in those with HFrEF, requiring further comparative investigations …”
Section: Discussionmentioning
confidence: 99%
“…Although many factors affect RDW, higher levels of RDW in patients with infection is a consequence of elevated inflammatory cytokines causing stress erythropoiesis and impaired maturation of red cells. Many investigations have used RDW on admission as a parameter predicting mortality and morbidity of HF, and some studies investigated serial changes of RDW during hospitalization . In‐hospital elevation of RDW is associated with increased mortality in HF patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation